ENT 530 Social Media Portfolio: Rubric / Nur Amirah Aisyah Mohammad Musa - Mohammad Musa, Nur Amirah Aisyah (2021)
Sweeetieepop is business that selling popcorn in a variety of flavours which is caramel popcorn, honey popcorn and toffee popcorn. We create a variety of flavours as our strategy to gain a lot of customers because customers have different taste. Our products packaging also very attractive which is we put it into a paper bag because cheaper, attractive and can decrease of using a plastic bag. Our product price also at an affordable price. Even we using premium ingredients but we manage to put affordable price for customers because we find the suppliers that offer cheaper price. The more customers buy popcorn per gram the cheaper price they will get. Therefore, mostly the customers that want to hold event such as wedding event will order from us because they can get a cheaper price. Our target customers are customers that like to eat sweet foods, love snacks, and goodies for event. Then, mostly children and students loves to eat popcorn because it is sweet foods and addictive. And students probably stay up until midnight to do assignment and need some snack to prevent sleepy. Not only that, people who love watching Netflix, television and YouTube also love popcorn. Furthermore, we use attractive graphics as marketing to promote our products. This tool very effective because people tend to see graphics than using a lot of words and caption. We also give a lot of information about the benefits of the ingredients. Not only, that we also give some tips and recipe that they can try it to advance the taste of popcorn.